المعرفة اللغوية الصحيحة من خلال وسائل الإعلام Talking About Proper Linguistic Knowledge Through The Media - الشرقاوي محمد; فتح الباب محمد (Université de M'sila, 2020)
ملخص: هذا البحث يتحدث عن المعرفة اللغوية الصحيحة من خلال وسائل الإعلام، ويحتوي علي مقدمة فيها: أهمية وسائل الإعلام، والحديث عن دعاوي التغريب واستخدام العامية، ومبحثين ، ثم الخاتمة ، وتكمن إشكالية البحث في أن الإعلام أصبح بوسائله المختلفة ضرورة لا غنى عنها ، فلا يمكن أن تعيش دولة منعزلة عن الدول الأخرى دون أن يكون بينهما وسائل اتصال، وله دور كبير يتنامى ويتعاظم، وحينما نعلم أن كثيرا من الشعوب تعاني من الحملات الإعلامية الهاجمة على عقيدتهم وهويتهم ندرك أن الإعلام ضرورة من ضرورات العصر ،ويهدف البحث إلى :أولا: : بيان أهمية وسائل الإعلام، ودعاوي التغريب واستخدام العامية، ثانيا: بيان أهمية الصحافة واستخدام العربية الفصحى الحديثة. وبيان مسؤولية الصحافة، وواجبها. ودور المجلات الثقافية في تنمية اللغة العربية، ثالثا: بيان واجب الإذاعة والإعلام المرئي في العالم العربي، وقد اعتمد البحث على المنهج الوصفي التحليلي، وفي النهاية مجموعة من النتائج أهمها: إظهار البحث أهمية الإعلام المرئي، ووضح سبل معالجة أخطائه. كلمات مفتاحية: المعرفة، اللغوية، الصحيحة، وسائل الإعلام. Abstract: This research talks about proper linguistic knowledge through the media, and contains an introduction to it: the importance of the media, And talk about claims to alienation and the use of colloquial, and two topics, then the conclusion, and the problem of research lies in the fact that the media has become by its various means an indispensable necessity, it is not possible to live a state isolated from other countries without having between them means of communication, And has a great role that grows and grows, and when we know that many people suffer from media campaigns that attack their faith and identity, we realize that the media is a necessity of the times, and the research aims to: Second: Explaining the importance of journalism and the use of modern Standard Arabic. And a statement of the responsibility of the press, and its duty. And the role of cultural magazines in the development of the Arabic language, third: Explaining the duty of radio and visual media in the Arab world, The research relied on the descriptive analytical approach, and in the end a set of results, the most important of which are: The research shows the importance of visual media, and explains ways to address its mistakes. Key words: knowledge, linguistic, correct, media
Keywords: المعرفة ، ; اللغوية ، ; الصحيحة ، ; وسائل الإعلام